The modelling of thermal behaviour of Kaolin clay at different temperatures / Adnan Abdullah and Zuraidi Hanafi Hanafi - Abdullah, Adnan; Hanafi, Zuraidi Hanafi (1996)
The lay public thinks of KAOLIN CLAY as artware and knows that the products of the earliest artisans were ceramics. The engineer also knows that ceramic materials are used in a wide usage of Hi-Tech products extending from mechanical properties, i.e. high-speed cutting tools, to electrical properties, i.e. piezoelectric transducers to high frequency magnets and optic fibers. Instead of using kaolin in the manufacturing of porcelain, firebrick, and China ware, Kaolin has also been exported on a small scale, for use as rubber filler in Malaysia since 1932. At present there are no proper investigation has been carried out to find the new breakthrough of Kaolin especially on engineering purposes. This project gives to us a new approach with the structure in Kaolin. After we get what's their behaviour, we can analyse the advantages of that clay and the new 'best product' will be produces respect to these. We hope that this project can be fruitful as a starting point of intensive research on Kaolin clay.